Temporal trends in incidence of time-loss injuries in four male professional North American sports over 13 seasons - Bullock, G. S.; Murray, E.; Vaughan, J.; Kluzek, S. (Scientific Reports, 2021)
Sports-related injuries increase healthcare cost burden, and in some instances have harmful long term physical and psychological implications. There is currently a lack of comprehensive data on temporal injury trends across professional North American sports. The purpose of this study was to compare temporal trends, according to incidence and time-loss injuries, by body part in professional baseball, basketball, football, and ice hockey. Public injury data from Major League Baseball, National Basketball Association, National Football League, and National Hockey League from 2007 to December 2019 were extracted and used. A mean of 62.49 injuries per 100 players per season was recorded for all professional sports. The groin/hip/thigh reported the greatest season proportional injury incidence for baseball, football, and ice hockey, with the groin/hip/thigh as the third highest injury incidence in basketball. When stratifying by more specific body part groupings, the knee demonstrated the greatest injury proportional incidence for basketball, football, and ice hockey, with the knee as the third highest proportional injury incidence for baseball. There was an increased in basketball ankle injuries following 2011-2012 season. Football and ice hockey reported the greatest concussion proportion incidence, with football demonstrating an increase in concussions over time, and a substantial increase in concussions from the 2014 to 2015 season. These publicly extracted data and findings can be used as a shared resource for professional baseball, basketball, football, and ice hockey for future individual and across sport collaborations concerning resource allocation and decision making in order to improve player health.